Radiological characteristics of pulverized fly ashes produced in Turkish coal-burning thermal power plants - Turhan, Şeref; Parmaksız, A.; Köse, A.; Yüksel, A.; Arıkan, İ.H.; Yücel, B. (Fuel 89 (2010) 3892–3900, 2010)
The objective of this study is to determine radiological characteristics of pulverized fly ash (PFA) collected from the 15 coal-burning thermal power plants (TPPs) in operation by means of gamma spectrometric technique and to assess the radiological impacts from the utilization of PFA samples examined as filling and cover material in earthwork applications. Also, the annual effective doses received by workers handling PFA and members of the public living in a house near the PFA pile/landfill were estimated using methods specified in the Radiation Protection 122. The activity concentrations of 226Ra, 232Th and 40K measured in PFA samples were tabulated for each TPP. The activity results show that Turkish PFA may have relatively high natural radioactivity content, depending on its origin reaching in the case of Kangal PFA 2720 Bq kg 1 of 226Ra. The values of external exposure indexes (radium equivalent activity index and gamma index) calculated for PFA samples are within the recommended safety limits. As well, the highest mean total annual effective doses estimated as 7.3 10 5 Sv y 1 for workers and 1.5 10 4 Sv y 1 for members of the public are significantly lower than the annual limit of 1.0 10 3 Sv y 1.
Keywords: Pulverized fly ash, Radioactivity, Gamma index, Annual effective dose, Earthwork applications